Two Cases of Vancomycin-Resistant Enterococcus faecium Bacteremia With Development of Daptomycin-Resistant Phenotype and its Detection Using Oxford Nanopore Sequencing. (23rd May 2020) - Udaondo, Zulema; Jenjaroenpun, Piroon; Wongsurawat, Thidathip; Meyers, Erik; Anderson, Courtney; Lopez, James; Mohan, Meera; Tytarenko, Ruslana; Walker, Brian; Ussery, David; Kothari, Atul; Jun, Se-Ran
Abstract: In this work, we report 2 cases of vancomycin-resistant Enterococcus faecium bacteremia with development of daptomycin resistance in 2 patients with acute myeloid leukemia and myelodysplastic syndrome. Mutations related to daptomycin-nonsusceptible phenotype in liaSR genes were found in all strains of the study, including those with a minimum inhibitory concentration <1 µg/mL collected before daptomycin therapy. Epidemiological investigation using core genome single nucleotide polymorphism and core genome multilocus sequence typing revealed clonality of all the isolates. In this study, we conclude that real-time genome sequencing of clinical isolates can provide rapid access to timely information on daptomycin-resistant genotypes that would help clinicians speed up and optimize the selection of the antibiotic for treatment.